2022
DOI: 10.3390/foods11030268
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Supplementation Improves Intestinal Permeability, Obesity Index and Metabolic Biomarkers in Elderly Thai Subjects: A Randomized Controlled Trial

Abstract: Intestinal integrity prevents the diffusion of allergens, toxins, and pathogens from the gastrointestinal lumen into the tissue and the circulatory system. Damage in intestinal integrity may cause mild to serious health issues, such as inflammation, gastrointestinal disorders, neurological diseases, and neurodegenerative disorders. Thus, maintaining a healthy intestinal barrier function is essential to sustain health. Probiotics are known for their ability to protect and restore intestinal permeability in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 44 publications
1
56
0
Order By: Relevance
“…An RCT reported in 2022 revealed that supplementation of the studied probiotics significantly improved the function of the intestinal barrier, leading to a significant reduction in concentrations of lipopolysaccharides (LPS). It also substantially increased HDL-cholesterol and SCFA levels (propionic and butyric acid) and improved obesity-related biomarkers [ 142 ]. Treatment with multispecies probiotics changed the biochemical, physiological, and immunological parameters of the gut microbiota in postmenopausal women with obesity but did not affect diversity or taxonomic classification [ 143 ].…”
Section: Influence Of Anti-inflammatory Diet On Gut Microbiota Insuli...mentioning
confidence: 99%
“…An RCT reported in 2022 revealed that supplementation of the studied probiotics significantly improved the function of the intestinal barrier, leading to a significant reduction in concentrations of lipopolysaccharides (LPS). It also substantially increased HDL-cholesterol and SCFA levels (propionic and butyric acid) and improved obesity-related biomarkers [ 142 ]. Treatment with multispecies probiotics changed the biochemical, physiological, and immunological parameters of the gut microbiota in postmenopausal women with obesity but did not affect diversity or taxonomic classification [ 143 ].…”
Section: Influence Of Anti-inflammatory Diet On Gut Microbiota Insuli...mentioning
confidence: 99%
“…51 When administered in sufficient amounts, they can exert various benefits, including regulating the gut microbiota, reducing the serum cholesterol, modulating the immune response, and repairing the cognitive impairment. 52,53…”
Section: The Antidepressant Mechanism Of Common Food Supplementsmentioning
confidence: 99%
“…Several studies reported that probiotics—particularly Lactobacilli and Bifidobacteria reduce symptoms associated with leaky gut by reducing inflammation, improving the intestinal barrier function, and by promoting the rapid restoration of the gut microbiota [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%